The farmer's daughter - Harrison, Jim (Grove Press, 2010)
Three novellas which give a portrait of three unconventional American lives.
Keywords: Domestic fiction; Fathers and daughters -- Fiction; Teenagers -- Fiction; Werewolves -- Fiction